Gas to liquid (GTL) role in diesel engine: Fuel characteristics and emission: A review - Mhadi A. Ismael; Mohd A.F. Rosli; A. Rashid A. Aziz; Salah E. Mohammed; Rasheed Adewale Opatola; Mohammed El-Adawy (Cleaner Engineering and Technology, 2024)
Gas to Liquid (GTL) fuel is considered a clean and alternative fuel and has been given much attention as a replacement for conventional fuels. This paper reviews and discusses the GTL fuel characteristics and the effects of GTL fuel on performance and emission in engines, considering previous research works. The properties of GTL fuel, such as a higher cetane number than diesel, improve its ignition and, therefore, burn more efficiently. It also helps to eliminate the knock and noise produced by the engine, resulting in lower emissions of pollutants. The energy density of GTL can potentially be higher than that of diesel, depending on its specific chemical composition and carbon cuts in the fuel, which provides more energy per unit volume, resulting in better brake-specific fuel consumption. The major finding is that the ability of GTL fuel to be implemented in existing ICE without significant modification should enhance the involvement of GTL in the automotive sector. GTL fuel has lower emissions of particulate matter, sulphur oxides, and nitrogen oxides, which are harmful pollutants that contribute to air pollution and respiratory problems. In contrast, the brake power from the usage of GTL has shown a lower value than diesel. This is caused by the lower volumetric heating value of the GTL fuel. The production process is expensive and requires significant energy, which may offset some of the environmental benefits. Additionally, the infrastructure for producing and distributing GTL fuel has yet to be widely available, which makes it difficult to adopt as a widespread replacement for conventional fuels.